What is minimum viable product? - LeMay, Matt (O'Reilly Media, Inc., 2018)
The Lean Startup movement has popularized the notion of "minimum viable product"--But what does it actually mean for today's organizations? This segment introduces the concept of "minimum viable product" with an emphasis on validating learning in real-world markets. This clip is taken from the original video course "Agile for Everybody-Prototypes and Minimum Viable Products for the Real World."